Analisis Pengaruh Kualitas Pelayanan Dan Penanganan Keluhan Terhadap Kepuasan Dan Loyalitas Nasabah Pada Bank Bnisyariah Semarang - Khoiri, Anzal Huda; Adityawarman, Adityawarman (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2021)
Business competition faced by Bank BNI Syariah in Semarang is very tight. With the increasing number of competitors, Bank BNI Syariah should increase loyalty level of its customers. This study aims to determine the impact of service quality and complaint handling on customer satisfaction and customer loyalty. Sample used in this research is 105 respondents, taken from customers of BNI Syariah in Semarang. Data were collected through questionnare and distributed by google form. Data that have been gathered then were processed using SPSS 23. Data analysis techniques used in this study are decriptive analysis and path analysis.The results of this study show that service quality and complaint handling have a positive and significant impact on customer satisfaction partially and simultaneously. Customer satisfaction has a positive and significant impact on customer loyalty. Based on path analysis, service quality and complaint handling do not have a direct impact on customer loyalty.